(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The development in training was not improvisation, but came as a result of the use of modern scientific methods in planning and training continuously. Based on this fact, the researcher adopted a hypothesis that supports the use of special physical exercises with the difference and diversity of these training exercises, which will thus be reflected in increasing the ability to adapt to the different requirements of play and the relationship of that on the development of basic skills in handball. Because of the lack of focus on exercises for physical abilities, the researchers decided to study this problem and develop appropriate solutions to it through the preparation of special physical exercises for physical abilities aimed at developing basic skills. The study aimed to: Preparing special exercises for physical abilities to develop some basic handball skills for young players. It aimed also to identify the extent of the impact of physical training in the development of some essential handball skills for young participants. The analysis assumed that there is a favorable outcome of training for physical abilities in the development of some basic handball skills for young players. The researcher used the experimental approach and the research sample was the players of Al-Qasim Club, junior category and to extract the results the researcher used the statistical bag (SPSS ) and through the results of the research were the following conclusions: The use of special exercises for physical abilities to develop basic skills in handball and that the exercises had an impact on physical abilities as well as basic skills.